Global Burden of Tracheal, Bronchus, and Lung Cancer in Adults Over 55 Years Old Based on Socio-demographic Status and Geographical and Gender Differences from 2010-2021 - Afrooz Mazidimoradi; Elham Shabani; Fatemeh Rezaei; Fariba Shahraki-Sanavi; Zahra Shahabinia; Leila Allahqoli; Hamid Salehiniya (Thoracic Research and Practice, 2025)
OBJECTIVE: This study presented the tracheal, bronchus, and lung cancer (TBLC) trend in adults ≥55 based on the Socio-demographic Index and geographical regions. MATERIAL AND METHODS: We obtained annual TBLC data from 2010 to 2021 from the 2021 Global Burden of Disease (GBD) Study and analyzed the incidence, death rates, and disability-adjusted life years (DALYs) rates across different geographical classifications of 204 national and territorial. RESULTS: In adults ≥55 years, the TBLC incidence rate decreased from 2010 to 2021 by globally 20.9% and 9.6% in males, while increasing by 3.8% in females. Approximately 60% of TBLC cases occurred in Asian countries. European countries exhibit the highest incidence rate (169.16 per 100,000). Males across all continents showed a decreasing trend, only the Americas reported a decreasing trend for women, with a noted change of 17.3%. The Western Pacific Region (World Health Organization region), East Asia (GBD region), Monaco, and countries with advanced health systems reported the highest incidence, death, and DALY numbers and rates for all genders. World Bank Upper middle-income countries recorded the highest DALY numbers and rates, incidence, and death numbers, all showing a downward trend, similar to high-income countries. CONCLUSION: The global burden of TBLC is predominantly in Asian countries (mainly East Asia), with a slower decrease in incidence, death, DALY, and burden rates. Therefore, reducing exposure to risk factors, expanding screening and diagnostic programs, especially for high-risk male smokers and females, and improving treatment procedures to reduce the progression of this cancer are urgent.